Oxygen effect on structural and optical properties of zinc oxide. (3rd June 2019) - Radjehi, Lamia; Djelloul, Abdelkader; Lamri, Salim; Slim, Mohamed Fares; Rahim, Mourad
ABSTRACT: This article deals with an investigation of the effect of oxygen content on optical and structural properties of ZnO films. Zinc oxide films were deposited with the DC reactive magnetron sputtering process on Si(100) and glass substrates. ZnO films were elaborated at different oxygen flow rates from (O2 ) 12 to 35 sccm. The evolution of optical and structural properties as a function of O2 was investigated by X-ray diffraction, Profilometer, Field Emission Scanning Electron Microscopy (FESEM) and ultraviolet–visible. By increasing O2, the crystallite size increases from 20 to 27 nm, which leads to an enlargement in the ZnO band gap from 3.18 to 3.30 eV. At 30 sccm of O2, the films present a significant improvement in the band gap (3.30 eV). The results reveal that with increasing O2, all films show a high crystallinity in the wurtzite phase and present a (002)ZnO preferential orientation along the c -axis. ZnO exhibited a good self-texture.